2020
DOI: 10.1002/smll.202000705
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial Transformation in the Soil–Plant System: Implications for Food Safety and Application in Agriculture

Abstract: Engineered nanomaterials (ENMs) have huge potential for improving use efficiency of agrochemicals, crop production, and soil health; however, the behavior and fate of ENMs and the potential for negative long‐term impacts to agroecosystems remain largely unknown. In particular, there is a lack of clear understanding of the transformation of ENMs in both soil and plant compartments. The transformation can be physical, chemical, and/or biological, and may occur in soil, at the plant interface, and/or inside the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 122 publications
(175 reference statements)
0
84
0
Order By: Relevance
“…The corona formed in leaves, soils, and from rhizospheres are currently unexplored, but elucidation of their composition will enable prediction of ENM uptake, development of plant sensors, and toxic response within major agricultural crops to help maintain food security with the increasing prevalence of ENMs in agricultural soils. 9,[102][103][104] Moreover, just as biomedical studies have identified proteins that target ENMs to key organs, so corona studies in plants can enhance efficacy of biopesticides through targeting and control of the corona. Further analysis of the role of the corona in ENM trophic transfer may also lead to guided reactivity of ENMs within specific plants or symbiotic microbes.…”
Section: Overcoming the Challenge Of Biodiversitymentioning
confidence: 99%
“…The corona formed in leaves, soils, and from rhizospheres are currently unexplored, but elucidation of their composition will enable prediction of ENM uptake, development of plant sensors, and toxic response within major agricultural crops to help maintain food security with the increasing prevalence of ENMs in agricultural soils. 9,[102][103][104] Moreover, just as biomedical studies have identified proteins that target ENMs to key organs, so corona studies in plants can enhance efficacy of biopesticides through targeting and control of the corona. Further analysis of the role of the corona in ENM trophic transfer may also lead to guided reactivity of ENMs within specific plants or symbiotic microbes.…”
Section: Overcoming the Challenge Of Biodiversitymentioning
confidence: 99%
“…As noted by Lowry et al, 8 many challenges and barriers need to be overcome before the real potential of nanomaterials (NMs) in agriculture can be achieved. A major barrier is that the interaction of NMs with plants, and the effects of these interactions on the behaviour of NMs, such as the transformations in the soil and at the soil/root interface and the uptake in plants, 19 as well as on the plant growth, are deeply interrelated and their exploration have only begun recently. Additionally, the environmental safety and human safety of NMs and their residues in plants and soil lack sufficient understanding currently.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a global effort to fabricate and utilise emerging nanomaterials, nanocomposites, and nanostructured materials with desirable characteristics for use in aqueous environments, such as biological uids, aquatic ecosystems, and agricultural soil. [1][2][3][4][5] The biocompatibility and sustainability aspects of the desired nanomaterials have been widely investigated with the aim of addressing concerns about how they behave in the mentioned environments. [6][7][8][9] Subsequent to this, understanding and controlling the nanostructure and nanoscale dynamics of materials is also important to the devices integrating these materials.…”
Section: Introductionmentioning
confidence: 99%